2011
DOI: 10.1111/j.1939-165x.2011.00304.x
|View full text |Cite
|
Sign up to set email alerts
|

Stability of hematologic analytes in monkey, rabbit, rat, and mouse blood stored at 4°C in EDTA using the ADVIA 120 hematology analyzer

Abstract: Although most of the changes in the hematologic analytes in blood from monkeys, rabbits, rats, and mice when samples were stored at 4°C were analytically acceptable and clinically negligible, the best practice in measuring hematologic analytes in these animals is timely processing of blood samples, preferably within 1 hour after collection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 17 publications
5
29
0
3
Order By: Relevance
“…Blood smear evaluation is also useful for evaluating other preanalytic artifactual changes, as time and temperature can also affect other cell lines . Numerous reports document time‐ and temperature‐dependent changes in RBCs, WBCs, and PLTs, and automated and manual CBC indices in cattle, lab animals, dogs, sheep, goats, horses, turkeys, and harp seals . However, surprisingly, in Xenopus tropicalis , using the Natt‐Herrick solution, cellular integrity was maintained for 2 years post collection …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood smear evaluation is also useful for evaluating other preanalytic artifactual changes, as time and temperature can also affect other cell lines . Numerous reports document time‐ and temperature‐dependent changes in RBCs, WBCs, and PLTs, and automated and manual CBC indices in cattle, lab animals, dogs, sheep, goats, horses, turkeys, and harp seals . However, surprisingly, in Xenopus tropicalis , using the Natt‐Herrick solution, cellular integrity was maintained for 2 years post collection …”
Section: Discussionmentioning
confidence: 99%
“…Evaluation and, therefore, interpretation of CBC findings can be limited by certain preanalytical factors. For example, prolonged storage could cause artifactual increases in hematocrit, MCV, and MPV, and decreases in the MCHC and PLT variables . Additionally, in 1984, Gossett and Carakostas showed that prolonged storage of blood in EDTA could cause the development of cytoplasmic vacuoles in neutrophils.…”
Section: Introductionmentioning
confidence: 99%
“…Sample stability is the ability of its analyte to maintain the initial value of the determined parameter. Analyte stability, however, may vary due to storage temperature of the sample, time elapsed since blood collection, animal species, and method of analysis (Ameri et al 2011).In this study, temperature of sample storage had no significant effect on analyte stability for all of the determined parameters (HCT, HGB, and RBC) regardless of the determination method (traditional or multi-parameter automated method). Based on other studies, temperature may have a different impact on sample stability in various mammalian species (Ihediohaet al 2007).…”
Section: Discussionmentioning
confidence: 55%
“…Use of a tube rocker will ensure that samples remain well mixed following collection and prior to analysis. Most hematology variables are stable at 4°C for up to 24 hours . Fresh blood smears should be prepared immediately, but at a maximum, within 6 hours of phlebotomy…”
Section: Summary Of Best Practice Recommendationsmentioning
confidence: 99%